1991
DOI: 10.1007/bf01313701
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of iron and nitrogen nutrition in the red tide dinoflagellateGymnodinium sanguineum

Abstract: Abstract. Iron-stress-mediated effects on biochemical constituents of the red tide dinoflagellate Gymnodinium sanguineurn Hirasaka were examined in 1988 by comparing Fe-replete and Fe-deplete batch cultures. The influence of nitrogen source (NO 3 or NH4) on characteristics of Fe-deplete cells was also studied [i.e., Fe-deplete/NO 3-grown (= -Fe/NO3) vs Fe-deplete/NH4-grown (= -Fe/ NH4) ]. Common to both N sources were reductions of chlorophyll a (chl a) and Fe quotas (per cell volume) by 75% and ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…In the preceding paper (Doucette and Harrison 1991), we demonstrated that iron depletion alters the biochemical composition of Gymnodinium sanguineum, a red tide species. However, both the extent and nature of these changes are, in fact, influenced strongly by nitrogen source (i.e., NO 3 or NH4).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…In the preceding paper (Doucette and Harrison 1991), we demonstrated that iron depletion alters the biochemical composition of Gymnodinium sanguineum, a red tide species. However, both the extent and nature of these changes are, in fact, influenced strongly by nitrogen source (i.e., NO 3 or NH4).…”
Section: Introductionmentioning
confidence: 85%
“…of Oceanography, University of British Columbia) were maintained on enriched artificial seawater as described in the preceding paper (Doucette and Harrison 1991). of Oceanography, University of British Columbia) were maintained on enriched artificial seawater as described in the preceding paper (Doucette and Harrison 1991).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron has been shown to be one of the essential trace elements required for the occurrence of massive blooms of dinoflagellates (Doucette and Harrison, 1991). Blooming of marine micro algae (Naito et al, 2008;Wegner et al, 2006) in coastal waters has been attributed to the assimilation of nutrients including iron, made available via land run-off and aeolian sources.…”
Section: Introductionmentioning
confidence: 99%